Sustainable construction through life cycle costing - F.A. Rahim,; S.A.Muzaffar,; N.S. Mohd Yusoff,; N. Zainon,; C. Wang, (Penerbit UKM, 2014)
Sustainable construction refers to the integration of environmental, social and economic considerations into construction business strategies and practices. It is the application of the principles of sustainable development to the comprehensive construction cycle from the extraction of raw materials, through the planning, design and construction of buildings and infrastructure, until their final demolition and management of the resultant waste. The implementation of Life Cycle Costing (LCC) in the sustainable construction industry is significantly important to construct the structures and infrastructure projects that will meet all the principles of sustainability. During the process of developing a project, LCC principles and techniques aim to provide best value from a whole life perspective. This paper, in reviewing the application of life cycle costing and sustainable construction, explores the correlation between these two elements and assesses how these can be used to achieve sustainability over the whole life of building projects.